Linking Entrepreneurial Intentions and Mindset Models: A Comparative Study of Public and Private Universities in Vietnam - Viet Quoc Cao; Tien Thanh Thi Ngo (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2019)
The main purpose of our study is to test the mindset model explored by Mathisen and Arnulf (2013). Based on Ajzen’s theory of planned behavior, the capacity theory, and the need for achievement theory, an extension model on the entrepreneurial intentions involving implementing mindset and elaborating mindset has been proposed. These constructs were confirmed in the proposed research model, including the need for achievement, perceived educational support, perceived structural support, perceived relational support and entrepreneurial intentions. The moderating role of gender, Grade Point Average (GPA) and the type of university were also tested. Research findings support that the need for achievement has a significant impact on the students’ mindsets and their entrepreneurial intentions. Elaborating the mindset, implementing the mindset and the perceived relational support significantly affect entrepreneurial intentions. The findings have contributed new ideas to the theoretical framework of entrepreneurship. They confirm the importance of the need for achievement in the relationship between the mindset and the entrepreneurial intentions of business students.